2004
DOI: 10.1637/5698
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Litter Beetles as Potential Reservoir for Salmonella enterica and Thermophilic Campylobacter spp. Between Broiler Flocks

Abstract: We evaluated the role of beetles infesting broiler chicken rearing facilities as potential reservoirs for Salmonella enterica infections between successive broiler flocks. In addition, their role as potential reservoirs for thermophilic Campylobacter spp. was also investigated. Fourteen broiler houses located at 11 different farms were included in the study. The houses were nonrandomly selected on the basis of their salmonella status; nine were persistently contaminated with salmonella whereas five were salmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 32 publications
4
51
1
5
Order By: Relevance
“…In this study, 90% of birds that consumed a single adult or larval beetle became C. jejuni positive, while 100% of those that consumed 10 adults or larvae became positive, a finding that suggests that beetles are capable of passing viable bacteria to chickens (388). In contrast, Skov and colleagues found that litter beetles, which are commonly present in chicken houses, do not play an important role as reservoirs of Campylobacter species (389). It is possible that only specific species of beetles are carriers of Campylobacter species.…”
Section: Other Sourcescontrasting
confidence: 51%
“…In this study, 90% of birds that consumed a single adult or larval beetle became C. jejuni positive, while 100% of those that consumed 10 adults or larvae became positive, a finding that suggests that beetles are capable of passing viable bacteria to chickens (388). In contrast, Skov and colleagues found that litter beetles, which are commonly present in chicken houses, do not play an important role as reservoirs of Campylobacter species (389). It is possible that only specific species of beetles are carriers of Campylobacter species.…”
Section: Other Sourcescontrasting
confidence: 51%
“…and Clostridium sp. (SKOV et al, 2004;VITTORI et al, 2007;HAZELEGER et al, 2008;JAPP et al, 2008;CHERNAKI-LEFFER et al, 2010).…”
Section: Abstract: Diatomaceous Earth (De) Is An Inert Powdermentioning
confidence: 99%
“…in poultry facilities. Bacteria have been found inside poultry housing units in the litter (Bhatia et al, 1979), water (Souza et al, 1992), bird feces (Gama et al, 2003), and lesser mealworms (Alphitobius diaperinus) (Skov et al, 2004). Equipment and materials kept outside of the housing units and away from the birds have also been tested positive for Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%